Effect of Four Wave Mixing on the Transmission Performance of WDM Solitons - Edmund, Kueh Boon Kiang (2002)
Transmission performance of optical solution pulses in the presence of fiber nonlinear effects is of great importance for future multi- channel wavelenght division multiplexed (WDM) communication system. This thesis investigates the impacts of fiber nonlinear effects on the performance of optical WDM system using solitons employing Intensity Modulation-Direct Detection ( IM-DD ) and Pulse Position Modulation ( PPM) format. An analytical approach is developed to evaluate the bit error rate (BER) performance of a WDM soliton transmission link taking into considerations the limitations imposed by four wave mixing ( FWM) in a single mode fiber and the beat noise componentsarising out of the beating of the signal and FWM noise at the output of the photodetector at the receiver front end. Apart from that , further investigation is carried out to find the variance and the probability density function of the timing jitter in soliton arrival time caused by the accumulated FWM noise in the transmission fiber. The impact of timing jitter due to FWM and the BER performance is also estimated. The analysis is further extended to multi-channel WDM system with solitons. Finally, the impact of FWM on the BER performance of WDM optical Pulse Position Modulation system using soliton pulses is also investigated analytically.